2008
DOI: 10.1007/s11239-008-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism is associated with shortened APTT and increased fibrinogen values in a general population of unselected outpatients

Abstract: Although clinical evidence supports a plausible association between thyroid disorders and venous thrombosis, reliable evidence is so far lacking on the potential biological mechanisms and neither temporary nor permanent thromboembolic risk factors were constantly identified. We performed a 2-years retrospective analysis to retrieve combined results of activated partial thromboplastin time (APTT), prothrombin time (PT), fibrinogen, and thyroid stimulating hormone (TSH), performed on outpatients over 15 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
(31 reference statements)
1
31
1
1
Order By: Relevance
“…The same authors documented a significant increase in plasma VWF:RCo and factor VIII coagulant activity and related antigen in 14 healthy volunteers after receiving a short-term L-T 4 therapy (56). We have recently shown that in a sample of 1329 unselected adult outpatients, those with hyperthyroidism had shortened APTT and higher plasma fibrinogen levels when compared with euthyroid patients, whereas no significant differences were observed between euthyroid patients and those with hypothyroidism, thus confirming that overt hyperthyroidism is associated with mild to moderate hypercoagulability (57). Finally, increased plasma factor X activity levels, another marker of a hypercoagulable state, were recently described by Erem et al in patients with subclinical hyperthyroidism (58).…”
Section: Hyperthyroidismmentioning
confidence: 77%
“…The same authors documented a significant increase in plasma VWF:RCo and factor VIII coagulant activity and related antigen in 14 healthy volunteers after receiving a short-term L-T 4 therapy (56). We have recently shown that in a sample of 1329 unselected adult outpatients, those with hyperthyroidism had shortened APTT and higher plasma fibrinogen levels when compared with euthyroid patients, whereas no significant differences were observed between euthyroid patients and those with hypothyroidism, thus confirming that overt hyperthyroidism is associated with mild to moderate hypercoagulability (57). Finally, increased plasma factor X activity levels, another marker of a hypercoagulable state, were recently described by Erem et al in patients with subclinical hyperthyroidism (58).…”
Section: Hyperthyroidismmentioning
confidence: 77%
“…In this setting, renal-graft thrombosis is a rare but devastating complication of renal transplantation that accounts for one-third to one-half of early graft losses, highlighting the importance of investigating pretransplant patients for hypercoagulable states, particularly those with short APTTs [9]. Another recent study has also shown that hyperthyroidism associated with increased thrombotic risk might similarly be associated with hypercoagulability due to shortened APTTs and increased fibrinogen [10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hyperthyroid patients are known to have an increased prevalence of shortened APTT and higher fibrinogen levels than those with normal thyroid function. Because prolonged APTT and PT results indicate a reduced coagulation response and a bleeding tendency, these findings indicate that hyperthyroidism might be associated with hypercoagulability [12] . Previous studies largely have explored patients with clinically overt hypo-or hyperthyroidism who appeared to have an increased risk of bleeding or thrombosis [13] .…”
Section: Discussionmentioning
confidence: 85%